Korean Celebrity Brand Ambassador in Indonesia Advertisement: A Study Exploring Figure of Speech and Communication Strategies - Ronauli, Maria Margaretha; Ansas, Velayeti Nurfitriana; Lubis, Arif Husein (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
Effective communication in advertisements hinges on clarity and relatability. Choosing the right figures of speech and communication strategies can significantly enhance the effectiveness of an advertisement. This study aims to identify the types of figures of speech and communication strategies technique used in advertisements featuring South Korean celebrity brand ambassadors for Indonesian product. Using a descriptive qualitative method based on the theories of Kim Wook Dong (2002) and Tatang (2016), data source were collected from advertisements on social media YouTube by using the method of listening to the note-taking technique. An interactive analysis model was used to analyze the data. Based by predetermined criteria, data was reduced to a total of nine Indonesian product advertisements with containing South Korean celebrity brand ambassadors from 2016 - 2023. The findings reveal that various figures of speech and communication strategies were employed to evoke consumer emotions in conveying the message and the purpose of the advertisement. By employing figures of speech that evoke emotions, advertisers can increase the effectiveness of their campaigns by strategically selecting linguistic elements that resonate with the target audience.